1988
DOI: 10.1021/la00081a024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydroquinone and related compounds adsorbed at Pt(111) from aqueous solutions: electron energy-loss spectroscopy, Auger spectroscopy, LEED, and cyclic voltammetry

Abstract: Tennessee Eastman Co., and Dow Coming Corp. for their generous support under the Presidential Young Investigator Award (Grant No. CPE-8351190). We thank Prof. C. B. Richardson of the University of Arkansas for his technical advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 0 publications
5
69
3
Order By: Relevance
“…According to theoretical estimates based on Van Der Waals radii, horizontal HQ should achieve a packing density of 0.309 nmol/cm 2 (3). Estimates based upon LEED patterns of HQ at ordered Pt(111) surfaces led to a packing density of 0.276 nmol/cm 2 (5). Experimental values from this study are within the margins defined by these two values in this low concentration range.…”
Section: Molecular Orientation Of Adsorbed Hqsupporting
confidence: 63%
See 2 more Smart Citations
“…According to theoretical estimates based on Van Der Waals radii, horizontal HQ should achieve a packing density of 0.309 nmol/cm 2 (3). Estimates based upon LEED patterns of HQ at ordered Pt(111) surfaces led to a packing density of 0.276 nmol/cm 2 (5). Experimental values from this study are within the margins defined by these two values in this low concentration range.…”
Section: Molecular Orientation Of Adsorbed Hqsupporting
confidence: 63%
“…A horizontal orientation of the adsorbed HQ molecule results from adsorption at HQ concentrations below 0.1 mM (3,5). According to theoretical estimates based on Van Der Waals radii, horizontal HQ should achieve a packing density of 0.309 nmol/cm 2 (3).…”
Section: Molecular Orientation Of Adsorbed Hqmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of Qu are approximately the same for the series of chlorophenols indicating a common mode of binding. If the molecules are assumed to bind in an orientation in which the plane of the phenol ring is parallel to the adsorbing surface the area covered is 1.2-1.85 m 2 /g assuming a surface area of 0.532 nm 2 /molecule (Lu, et al, 1988). Since the surface area of the kaolinite is 6.9 m 2 /g only a portion of the surface is covered with phenol.…”
Section: Iii2 Experimental Resultsmentioning
confidence: 99%
“…Pd(110), 13 Au(111), 14 and Pt(111), 15,16 theoretical studies are limited to Rh(111) and Pt(111), 17,18 Ni(111), Ni(110) and Ni(221), 19,20 and Pd(111). 18,21 Most of these studies reported that while the C-ring of PL and PX was nearly parallel to the surface plane on Cu(110), Ni(111), 12 and Pt(111), 16 PX has tilted geometries on Ag(110) 8 and Mo(110).…”
mentioning
confidence: 99%